Autophagy activation attenuates the neurotoxicity of local anesthetics by decreasing caspase-3 activity in rats - Xue,Xing (2020)
Abstract Background and objectives The mechanisms by which local anesthetics cause neurotoxicity are very complicated. Apoptosis and autophagy are highly coordinated mechanisms that maintain cellular homeostasis against stress. Studies have shown that autophagy activation serves as a protective mechanism in vitro. However, whether it also plays the same role in vivo is unclear. The aim of this study was to explore the role of autophagy in local anesthetic-induced neurotoxicity and to elucidate the mechanism of neurotoxicity in an intrathecally injected rat model. Methods Eighteen healthy adult male Sprague-Dawley rats were randomly divided into three groups. Before receiving an intrathecal injection of 1% bupivacaine, each rat received an intraperitoneal injection of vehicle or rapamycin (1 mg.kg-1) once a day for 3 days. The pathological changes were examined by Haematoxylin and Eosin (HE) staining. Apoptosis was analysed by TdT-mediated dUTP Nick-End Labelling (TUNEL) staining. Caspase-3, Beclin1 and LC3 expression was examined by Immunohistochemical (IHC) staining. Beclin1 and LC3 expression and the LC3-II/LC3-I ratio were detected by western blot analysis. Results After bupivacaine was injected intrathecally, pathological damage occurred in spinal cord neurons, and the levels of apoptosis and caspase-3 increased. Enhancement of autophagy with rapamycin markedly alleviated the pathological changes and decreased the levels of apoptosis and caspase-3 while increasing the expression of LC3 and Beclin1 and the ratio of LC3-II to LC3-I. Conclusions Enhancement of autophagy decreases caspase-3-dependent apoptosis and improves neuronal survivalin vivo. Activation of autophagy may be a potential therapeutic strategy for local anaesthetic-induced neurotoxicity.